Addition of Vancomycin to Cefazolin Prophylaxis Is Associated With Acute Kidney Injury After Primary Joint Arthroplasty - Courtney, P. Maxwell (Clin Orthop Relat Res, 2014)
BACKGROUND: With increasing prevalence of methicillin-resistant Staphylococcus aureus (MRSA) in patients undergoing hip and knee arthroplasty, some have advocated a dual-antibiotic regimen including vancomycin as prophylaxis against surgical site infections. However, routine administration of vancomycin may result in impaired renal functions in susceptible patients. QUESTIONS/PURPOSES: The purpose of this study was to determine whether patients receiving antibiotic prophylaxis with cefazolin and vancomycin have a higher risk of postoperative acute kidney injury (AKI) compared with patients receiving cefazolin alone before elective primary hip and knee arthroplasty. We also aimed to compare severity and recovery of AKI in these two cohorts and to determine independent risk factors for AKI. METHODS: We retrospectively evaluated a series of 1828 patients undergoing primary hip and knee arthroplasty over a 2-year period who received either cefazolin (n = 500) or cefazolin and vancomycin (n = 1328) as perioperative antibiotic prophylaxis. During the study period, a perceived high prevalence of MRSA infections at our institution led some surgeons to add vancomycin to the prophylactic antibiotic regimen. The patient characteristics, case mix, and preoperative renal function and baseline creatinine clearance were similar between the two groups. We defined AKI according to the published Acute Kidney Injury Network (AKIN) criteria, and the risk of AKI in both groups was compared. We also compared the proportions of patients by AKIN severity stage and assessed recovery as defined by creatinine levels showing kidney function reaching 50% baseline. The American Society of Anesthesiologists (ASA) classification, preoperative chronic kidney disease, intraoperative fluid requirements, and estimated blood loss were recorded. We analyzed the data using a multivariate logistic regression model to identify potential independent risk factors, including dual antibiotic therapy. RESULTS: Patients receiving dual antibiotics were more likely to develop AKI compared with those receiving cefazolin alone (13% versus 8%, p = 0.002). Dual-antibiotic prophylaxis also was associated with greater severity; patients in the dual antibiotic group had higher rates of Grade II and III acute kidney injury (3% versus 0%, p = 0.003). There was no difference in the rate of return to baseline renal function (2 ± 1.4 days versus 3 ± 3.4 days; mean difference, 0.5 days; 95% confidence interval [CI], −0.2 to 1.2 days; p = 0.155). Controlling for confounding variables, dual antibiotic prophylaxis (adjusted odds ratio [OR], 1.82; 95% CI, 1.25–2.64; p = 0.002), ASA class (adjusted OR, 1.64; 95% CI, 1.24–2.17; p = 0.001), and preoperative kidney disease (adjusted OR, 1.81; 95% CI, 1.30–2.52; p = 0.001) were independent risk factors for AKI after primary total joint arthroplasty. CONCLUSIONS: Without a clear advantage in reducing surgical site infections, the utility and safety of routine addition of vancomycin to the prophylactic regimen in all patients undergoing primary hip and knee arthroplasty should be avoided. Further prospective studies should look at the efficacy of preoperative MRSA screening, decolonization, and selective use of vancomycin in high-risk patients. LEVEL OF EVIDENCE: Level III, therapeutic study.